Growth of Cajuput (Melaleuca leucadendron Linn.) and Longkida (Nauclea orientalis Linn.) in Flooded Condition of Acid Mine Water - Miftahul Mawaddah; Irdika Mansur; Lana Saria (Jurnal Silvikultur Tropika, 2012)
Coal   mining   in   Indonesia  mostly   are   conducted  using  open   pit   mining   system.   The   method   causing exposure  of mineral sulphide and triggered the production  of acid mine drainage (AMD) when oxidized by O2  and met with water. The problem is encountered by most companies  engaged in the coal mining, including PT. Mandiri Intiperkasa. An effort for handling  the   AMD    has   been   done  by establishment  of settling pond   that   was   planted   with   tifa   grass (Typha angustifolia).  The   grass   has   been   khown   for   its ability   to   neutralize   pH   and   at   the   same   time   absorb heavy   metals. However, in term of a long term use of the so called wetland area, it is regarded as non-productive  approach. Therefore, it need to sought types of commercial trees species that could survive and grow productively in wetland area to treat the AMD.          Treatments were asfollows: a. a combinat ion of species of tifa grass and cajuput (Melaleuca leucadendron Linn.); b. tifa  and  longkida   (Nauclea   orientalis   Linn.),   and  c. tifa  only.   Seedlings  were  observed  for  four  weeks.  Variables observed were: diameter growth, high growth, pH of the AMD, the weight of dried plants, the ratio (apa?), the roots and shoot nutrient analyses, and analysis of mud. The increase in the pH of AMD occurs every week on each unit test. Both types either cajuput and longkida able to survive and grow well for four weeks in the wet land flooded with AMD.